"Kompetenz" and "Beruf" in the context of the proposed German Qualifications Framework for Lifelong Learning - Gehmlich, Volker [Verfasser] (My University, 2009)
"The purpose of this paper is to answer a set of questions related to 'Kompetenz', 'Beruf' and the German Qualifications Framework for Lifelong Learning. What is a competence, can it be measured? Is the 'Beruf' really endangered by the focus on learning outcomes? What are the implications as regards the learning process? Are permeability and mobility between occupations fostered? It is assumed that 'Beruf' will also be used in future but in different contexts. It will describe any type of occupation or profession without the need to specify the way to get there ('Berufsbild'). Instead, there will be flexible pathways, allowing for non-formal and informal learning. Its former role of structuring training will be taken over by 'Kompetenz' within the qualifications frameworks. It is recommended to clearly differentiate between learning outcomes and "Kompetenz"." (Autorenreferat, BIBB-Doku)
Keywords: I 1.2 Anrechnung im Ausland erworbener Leistungen & Abschlüsse; L 6.3.1 Diagnose- & Messinstrumente; I 2.2 Europa; Kompetenz; Beruf; Begriff; Kompetenzfeststellung; Deutscher Qualifikationsrahmen; Europäischer Qualifikationsrahmen; Anrechnung von Bildungsleistungen; Lernergebnisorientierung